Influence of water run training on the maintenance of aerobic performance - Wilber, R. L.; Moffatt, R. J.; Scott, B. E.; Lee, D. T.; Cucuzzo, N. A. (Medicine & Science in Sports & Exercise, 1996)
The purpose of this study was to examine the effect of a 6-wk deep water running program on the maintenance of cardiorespiratory performance (VO2max, ventilatory threshold, running economy); metabolic measurements of blood glucose, blood lactate, and plasma norepinephrine; and body composition. Sixteen trained male runners (VO2max = 58.6 +/- 3.6 ml.kg-1.min-1) were assigned to one of two groups matched by VO2max, treadmill run (R) or water run (WR). Subjects participated in their respective training programs, which consisted of workouts of a) 30 min at 90-100% VO2max and b) 60 min at 70-75% VO2max alternated daily for 5 d.wk-1. Following 6 wk of workouts, no significant intra- or intergroup differences were observed for treadmill VO2max for R (pre = 58.4 +/- 2.3, post = 60.1 +/- 3.6 ml.kg-1.min) and WR (pre = 58.7 +/- 4.7, post = 59.6 +/- 5.4 ml.kg-1.min-1). Similarly, ventilatory threshold was unaltered in R (pre = 47.5 +/- 1.8, post = 48.2 +/- 3.3 ml.kg-1.min-1) and WR (pre = 46.5 +/- 6.4, post = 47.4 +/- 6.7 ml.kg-1.min-1), nor were there any changes in running economy in R (pre = 48.4 +/- 2.3, post = 48.9 +/- 2.0 ml.kg-1.min-1 at 255 m.min-1) and WR (pre = 51.8 +/- 2.0, post = 48.9 +/- 2.2 ml.kg-1.min-1 at 255 m.min-1). No significant differences were observed within or between groups for maximal blood glucose, blood lactate, and plasma norepinephrine concentration as well as for body composition indices. It was concluded that deep water running may serve as an effective training alternative to landbased running for the maintenance of aerobic performance for up to 6 wk in trained endurance athletes.